Supplementation of inactivated influenza vaccine with norovirus P particle-M2e chimeric vaccine enhances protection against heterologous virus challenge in chickens. - Mohamed Elaish; John M Ngunjiri; Ahmed Ali; Ming Xia; Mahmoud Ibrahim; Hyesun Jang; Jagadish Hiremath; Santosh Dhakal; Yosra A Helmy; Xi Jiang; Gourapura J Renukaradhya; Chang-Won Lee (PLoS ONE)
The current inactivated influenza vaccines provide satisfactory protection against homologous viruses but limited cross-protection against antigenically divergent strains. Consequently, there is a need to develop more broadly protective vaccines. The highly conserved extracellular domain of the matrix protein 2 (M2e) has shown promising results as one of the components of a universal influenza vaccine in different animal models. As an approach to overcome the limited, strain specific, protective efficacy of inactivated influenza vaccine (IIV), a combination of recombinant M2e expressed on the surface of norovirus P particle (M2eP) and IIV was tested in chickens. Co-immunization of birds with both vaccines did not affect the production of M2e-specific IgG antibodies compared to the group vaccinated with M2eP alone. However, the co-immunized birds developed significantly higher pre-challenge hemagglutination inhibition antibody titers against the homologous IIV antigen and heterologous challenge virus. These combined vaccine groups also had cross reactive antibody responses against different viruses (H5, H6, and H7 subtypes) compared to the IIV alone vaccinated group. Upon intranasal challenge with homologous and heterologous viruses, the combined vaccine groups showed greater reduction in viral shedding in tracheal swabs compared to those groups receiving IIV alone. Moreover, M2eP antisera from vaccinated birds were able to bind to the native M2 expressed on the surface of whole virus particles and infected cells, and inhibit virus replication in vitro. Our results support the potential benefit of supplementing IIV with M2eP, to expand the vaccine cross protective efficacy.